2017
DOI: 10.3390/f8090344
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Plant Species Richness and Terrain in Middle Sub-Tropical Eastern China

Abstract: Abstract:The objective of this research was to study the relation between species richness and topography in the middle sub-tropical area of Eastern China. A species richness survey was conducted along altitude in Kaihua County, Zhejiang Province, Eastern China. Topographic variables, such as altitude, slope, aspect, terrain roughness, relief degree and the topographical wetness index, were extracted from the digital elevation model. The Generalized Additive Model (GAM), the linear model and the quadratic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…GAMs are generalized models with smoothers and link functions based on an exponential relationship between the response variable and the predictor variables (Zuur et al, 2014b). GAMs have previously been used to model relationships between environmental variables and species richness (Robert et al, 2015;Song and Cao, 2017) and to identify ecological response thresholds (Foley et al, 2015;Large et al, 2015). GAMs were chosen because they can accommodate non-linear relationships and produce ecologically intuitive outputs by identifying the shape and strength of the relationship between the response and predictor variables (Zuur et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…GAMs are generalized models with smoothers and link functions based on an exponential relationship between the response variable and the predictor variables (Zuur et al, 2014b). GAMs have previously been used to model relationships between environmental variables and species richness (Robert et al, 2015;Song and Cao, 2017) and to identify ecological response thresholds (Foley et al, 2015;Large et al, 2015). GAMs were chosen because they can accommodate non-linear relationships and produce ecologically intuitive outputs by identifying the shape and strength of the relationship between the response and predictor variables (Zuur et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Pixels with higher TWI values have higher capacity of water accumulation (Besnard et al, 2013) or, in other words, being "wetter". The index is highly correlated with several soil attributes such as horizon depth, silt percentage, organic matter content, and phosphorus (Moore et al, 1993), can be used to simulate the status of soil moisture, which also has an influence on soil pH (Song, Cao, 2017). In our case, increasing values of TWI in relation to projected habitat suitability show a steady downward trend (Figure 3), meaning habitats that are "too wet" do not favour the species.…”
Section: Topographic Variablesmentioning
confidence: 99%
“…(8,10,34) Song and Cao reported that elevation and wetness significantly correlate with tree species richness. (35) Gonzalez and Mata reported that tree species richness and diversity correlate with elevation and slope, which are important factors for predicting tree species richness and diversity. (36) On the other hand, slope is expressed as one of the eight directions, and cannot be digitalized; thus, in this study, calculations were performed using the northern slope, which can be digitalized.…”
Section: Topographic and Geographic Factorsmentioning
confidence: 99%